The antihypertensive effect of ethyl acetate extract from red raspberry fruit in hypertensive rats - Jia, Han (Medknow Publications, 2011)
OBJECTIVES: To evaluate the antihypertensive effect of Xinjiang red raspberry fruit ethyl acetate extract (EER) on spontaneously hypertensive rats (SHR) and its possible mechanism from antioxidant perspective. MATERIALS AND METHODS: The SHR rats were randomly divided into 3 groups, and treated with EER low dose (EERL, 100 mg/kg/d), high dose (EERH, 200 mg/kg/d), and water (SHR) through gastric gavage daily for 5 weeks. Another 8 age-matched male Wistar–Kyoto rats were used as normotensive group (WKY). The systolic blood pressure (SBP) was measured by noninvasive tail-cuff method once a week. At the end of the treatment, blood samples were collected and serum concentrations of nitric oxide (NO), superoxide dismutase (SOD), malondialchehyche (MDA), and plasma endothelin (ET) were determined. RESULTS: Treatment of SHR rats with EER lowered the blood pressure compared with that treated with water (SHR), and the high dose showed more significant reduction in blood pressure. Treatment of SHR rats with EER increased serum NO and SOD levels and lowered ET and MDA levels. As compared with control group, NO levels were increased significantly in EERL (P < 0.01), SOD was elevated more significantly in both EERL and EERH (P < 0.01); MDA was decreased significantly in EERH group (P < 0.05), whereas plasma ET decreased more significantly in the EERH group (P < 0.05). CONCLUSIONS: The red raspberry extracts demonstrated a dose-dependent antihypertensive effects in SHR and this may be related to increased NO activation and improved vascular endothelial dysfunction via antioxidation. These results confirmed that raspberries rich in polyphenols have potential cardiovascular protective effects.